2016
DOI: 10.1007/s12603-015-0653-2
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and anti-neoplastic treatment in adult and older subjects - A systematic review

Abstract: Plausible pathophysiological pathways linking body composition, toxicity, and pharmacokinetics are sustained by the actual review. However, despite the growing number of older cancer patients, our review highlighted the lack of specific studies in the field of anti-neoplastic agents toxicity regarding body composition conducted in elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 81 publications
1
24
0
2
Order By: Relevance
“…This could result in overdosing in patients with sarcopenic obesity because of their high body surface area and decreased muscle mass, as reported in previous studies. 10,20,34,36 In our study, we found that BMI did not differ between CT 1 and CT 2 although muscle mass decreased significantly, which supports earlier findings stating that muscle mass is not necessarily associated with BMI and that loss of muscle mass could be accompanied by growth of adipose tissue. 13,35 Accordingly, there were significantly more patients with sarcopenia and sarcopenic obesity at the time of the evaluation CT scan than at the pre-treatment scan.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This could result in overdosing in patients with sarcopenic obesity because of their high body surface area and decreased muscle mass, as reported in previous studies. 10,20,34,36 In our study, we found that BMI did not differ between CT 1 and CT 2 although muscle mass decreased significantly, which supports earlier findings stating that muscle mass is not necessarily associated with BMI and that loss of muscle mass could be accompanied by growth of adipose tissue. 13,35 Accordingly, there were significantly more patients with sarcopenia and sarcopenic obesity at the time of the evaluation CT scan than at the pre-treatment scan.…”
Section: Discussionsupporting
confidence: 90%
“…A possible explanation is that oxaliplatin is a lipophilic agent and accumulates in the fat tissue compartments. In patients with excess fat, this may result in longer exposure to the drug that could lead to increased risk of neuropathy in sarcopenic obesity patients . Currently, dosing chemotherapy is performed base on body surface area, which is based on a patient's height and weight and used as an index for chemotherapy dosing, without taken body composition into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malnutrition is associated with increased chemotherapy toxicity in various malignancies, including breast cancer, colorectal cancer, renal cancer, and other solid tumors [3, 11, 13-15, 17, 19, 22]. However, limited data are available on the role of BMI as a risk factor for toxicity in patients with STS treated with trabectedin.…”
Section: Discussionmentioning
confidence: 99%
“…The balance of evidence from these studies suggests that low BMI and/or low lean body mass and sarcopenia are associated with dose-limiting toxicity [3, 11, 13-15, 17, 19, 22]. …”
Section: Introductionmentioning
confidence: 99%